2004
DOI: 10.1038/sj.bjc.6602215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of action and prediction of response to oxaliplatin in colorectal cancer cells

Abstract: The platinum compound oxaliplatin has been shown to be an effective chemotherapeutic agent for the treatment of colorectal cancer. In this study, we investigate the molecular mechanisms of action of oxaliplatin to identify means of predicting response to this agent. Exposure of colon cancer cells to oxaliplatin resulted in G2/M arrest and apoptosis. Immunofluorescent staining demonstrated that the apoptotic cascade initiated by oxaliplatin is characterised by translocation of Bax to the mitochondria and cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
167
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(190 citation statements)
references
References 42 publications
11
167
2
3
Order By: Relevance
“…So, we utilized HCT116 Bax wildtype and null isogenic cell lines to test our hypothesis. Earlier characterisation of HCT116 cell lines indicated that cells lacking Bax are resistant to TRAIL and are significantly less sensitive to chemotherapy (Zhang et al, 2000;Arango et al, 2004). In contrast to Bax wild-type colorectal cancer cell lines, we found that FLIP silencing did not induce cell death in HCT116 cells lacking Bax.…”
Section: Discussioncontrasting
confidence: 55%
“…So, we utilized HCT116 Bax wildtype and null isogenic cell lines to test our hypothesis. Earlier characterisation of HCT116 cell lines indicated that cells lacking Bax are resistant to TRAIL and are significantly less sensitive to chemotherapy (Zhang et al, 2000;Arango et al, 2004). In contrast to Bax wild-type colorectal cancer cell lines, we found that FLIP silencing did not induce cell death in HCT116 cells lacking Bax.…”
Section: Discussioncontrasting
confidence: 55%
“…The factors determining a p53-dependent apoptotic or cytostatic response to cytotoxic insult remain unclear. Recently, elevated cMyc levels have been identified as one such factor favouring a p53-dependent apoptotic response (Seoane et al, 2002 Despite significant progress in the identification of markers predicting response to other chemotherapeutic agents commonly used in the treatment of colorectal malignancies, namely, 5FU and oxaliplatin (Augenlicht et al, 1997;Salonga et al, 2000;Arango et al, , 2003Park et al, 2001;Shirota et al, 2001), there is a great need for clinical predictors of response to camptothecin derivatives. The capability of predicting response to the chemotherapeutic agents available for the treatment of colorectal cancer would allow tailoring of treatment to individual patients, thus maximising the probability of optimal response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The camptothecin derivative has been shown to be a useful chemotherapeutic agent for the treatment of colorectal cancer patients, improving response rates and survival when used in combination with 5FU, and has also been shown to be effective in 5FU-resistant tumours (Cunningham et al, 1998;Douillard et al, 2000;. Recently, there has been significant progress in the identification of genetic markers that allow prediction of response to 5FU and/or oxaliplatin, which together with CPT-11 are the main chemotherapeutic agents used in the treatment of colorectal cancer (Augenlicht et al, 1997;Salonga et al, 2000;Arango et al, , 2003Park et al, 2001;Shirota et al, 2001). However, there is great need for markers predicting the efficacy of CPT-11 treatment.…”
mentioning
confidence: 99%
“…The apoptotic pathway of colon cancer cells after exposure to oxaliplatin involves caspase 3 activation, translocation of Bax in the mitochondria, and release of cytochrome C in the cytosol 8 .…”
Section: Dna Lesionsmentioning
confidence: 99%